Graphic organizers and the speaking skills in 8th graders at unidad educativa Alberto Perdomo Franco during the school year 2018-2019 - Calva Castillo, Karina Fabiola (2019)
During the last three decades, many educators have been promoting the importance of meaningful learning in students by using different sorts of pedagogical resources. Graphic organizers are visual representation of knowledge that characterize ideas, thoughts, concepts, and among others. Barron was the one who introduced the term "Graphic Organizers" based on Ausubel’s theory and he states its relevance of this tools as to highlights the relationships between concepts and the level of abstraction in order to comprehend texts, vocabulary and meaning. Graphic Organizers can be used to improve students' thought development, foster brainstorming, generate new ideas, connect parts of a whole, draw sequences, and analyze causes and effects, among others. The use of graphic organizers will be essential to make speaking class more attractive and easier to understand, especially when students are beginning to study a foreign language. The present project presents this didactic tool based on the use of graphic organizers as support to develop speaking skills, relying on various theories as to guide teachers and students in the use of new instruments, improve oral communication in 8th grade students, at Unidad Educativa Alberto Perdomo Franco……